Impact of exponential form of internal heat generation on water-based ternary hybrid nanofluid flow by capitalizing non-Fourier heat flux model - K, Sarada; Gamaoun, Fehmi; Abdulrahman, Amal; Paramesh, S.O; Kumar, Raman; G D, Prasanna; Punith Gowda, R.J. (Case studies in thermal engineering, 2022)
The flow of fluids containing nanoparticles is important in industrial applications, particularly in nuclear reactors and nuclear system cooling to enhance energy efficiency. In connection to this, the convective boundary layer flow of ternary hybrid nanofluid (water-based graphene-CNT-Silver) flow over a curved stretching sheet with activation energy is investigated in this article. In addition, the non-Fourier heat flux model is taken into account. The use of similarity variables transforms the existing partial differential equations into an ordinary differential equation, which is then numerically solved using the Runge-Kutta-Fehlberg fourth and fifth order (RKF-45) method combined with a shooting approach. The set of graphical results for the significant parameters on thermal, concentration, and velocity profiles is explored. Results reveal that the heat transport in ternary hybrid nanoliquid rises as the thermophoresis and Brownian motion parameters rise. The Biot number influences the thermal profile positively, whereas the increasing Schmidt number and Stefan blowing parameter values reduce mass transport. The curvature parameter has positive impact on skin friction and mass transport rate but negative impact on heat transport rate. The concentration profile rises with increased activation energy parameter, but declines with increased chemical reaction rate parameter.